PERAN KEUNGGULAN BERSAING DALAM MEMEDIASI PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN - Wiratama Putra, I Made Yoga; Wulandari Kusumadewi, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023DO - 10.24843/EEB.2023.v12.i04.p14, 2023)
Marketing performance is a measure of a company to find out consumer needs and build relationships with consumers to achieve organizational goals in achieving company profits. Every business venture has an interest in proving the performance achieved with the achievement standards that have been prepared and agreed upon within the organization. Standardization of performance measures becomes important as a guide to assess the performance of a business. This study aims to determine the role of competitive advantage in mediating the effect of market orientation on marketing performance (study on apparel SMEs in Denpasar). This study used a sample of 50 apparel SMEs in Denpasar City. The method used in this study is a survey method with a questionnaire technique and interviews with statistical analysis tools inferential path analysis. The results of this study indicate that market orientation has a positive and significant effect on the marketing performance of apparel SMEs in Denpasar City. Market orientation has a positive and significant impact on the competitive advantage of apparel SMEs in Denpasar City. Competitive advantage has a positive and significant impact on the marketing performance of apparel SMEs in Denpasar City. Competitive advantage is a variable mediating the influence of market orientation on the marketing performance of apparel SMEs in Denpasar City.